PROTECTION OF DOMESTIC VIOLENCE VICTIMS PURSUANT TO LAW NUMBER 23 OF 2004 - Rachmat Ihya (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
In order to realize this wholeness and harmony, it really depends on everyone in the household, especially the level of quality of behavior and self-control of everyone in the household. The integrity and harmony of the household can be disrupted if the quality and self-control cannot be controlled, which in the end can lead to domestic violence resulting in insecurity or injustice to people in the household environment. To prevent, protect victims, and take action against perpetrators of domestic violence, the state and society are obliged to carry out prevention, protection and prosecution of perpetrators in accordance with the philosophy of Pancasila and the 1945 Constitution. The state is of the view that all forms of violence, especially domestic violence, are violations of human rights. Humans and crimes against human dignity and dignity as well as forms of discrimination. The problem approach used in writing this thesis uses a normative juridical approach, meaning that a scientific study conducted based on studying the law will identify several legal aspects and the basic principles that develop in these provisions.